Transformasi Pembelajaran Bahasa Indonesia di Sekolah Dasar melalui Pendekatan Deep Learning - Yoma Hatima (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The transformation of education in the digital era demands renewed learning strategies, including in Indonesian language lessons in elementary schools. One emerging innovative approach is deep learning, a form of in-depth learning that emphasizes conceptual understanding, critical reflection, and the connection of knowledge to students' real-life experiences. This study aims to explore the implementation of the deep learning approach in Indonesian language instruction in elementary schools, specifically at SD Negeri 2 Bojongmenteng, and its impact on improving students' literacy competencies. The method used was qualitative research with a case study approach. Data collection techniques included classroom observations, teacher and student interviews, and analysis of learning documents. The results indicate that the deep learning approach is able to increase active student participation, deepen text comprehension, and facilitate critical and creative thinking skills. Project-based learning, digital media integration, and structured reflection are key to the successful implementation of this approach. However, challenges such as teacher preparedness, limited facilities, and the need for digital pedagogy training remain obstacles. This study recommends strengthening teacher competencies in designing deep learning-based lessons and providing supporting resources. Thus, the transformation of Indonesian language instruction in elementary schools can be more meaningful and relevant to the demands of the 21st century.